The Performance of Unit Trust Industry in Malaysia - Shari, Aminah (Information Management and Business Review, 2015)
This study measured the efficiency of fixed income unit trust funds and equity unit trust funds for the period of January 2004 to December 2014. A total of 36 fixed income funds and 109 equity funds were evaluated using stochastic frontier analysis (SFA) technique with three inputs (expense ratio, portfolio turnover ratio, and fund management stated fee) and one output variable (return). The econometric technique was used to measure the portfolio efficiency score as well as to compare the efficiency of fixed income funds and equity funds. The results indicated that the average efficiency score for equity unit trust funds was higher than fixed income unit trust funds. Nevertheless, when the samples were categorized into panel data, the average efficiency score for fixed income funds increased throughout ten years. Meanwhile the average score for equity funds was consistent over the years. It shows that time is invariant for equity funds. However, this means that the performance efficiency for both types of funds was considered excellent and efficient. The results indicate that the mean efficiency achieved in unit trust industry is almost 100% of its potential output.